Control of base pressure with micro jets:part-I - Rehman, Shafiqur; Khan, Sher Afghan (Emerald Group Publishing, 2008)
This paper aims to present the results of an experimental investigation carried out to control the base pressure in a suddenly expanded axi-symmetric passage.Four micro-jets of 1mm orifice diameter located at 908 interval along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region was employed as active controls. The test Mach numbers were 1.25, 1.3, 1.48, 1.6, 1.8, 2.0, 2.5 and 3.0. The jets were expanded suddenly into an axi-symmetric tube with cross-sectional area 4.84 times that of nozzle exit area. The length-to-diameter ratio of the sudden expansion tube was varied from 10 to 1. Nozzles generating the above jet Mach numbers were operated with nozzle pressure ratio in the range 3-11. As high as 40 per cent increase in base pressure was achieved. In addition to base pressure, the wall pressure in the duct was also measured. Findings – It is found that the wall pressure is not adversely influenced by the micro jets. Originality/value – The paper provides information on internal supersonic flow.